Mandarin language teaching and learning in two Indonesian public universities / Du Yu - Du , Yu (2024)
Indonesia is a country in Southeast Asia with a large Chinese community that includes many native Chinese language speakers. In Indonesia, Chinese language education has undergone a tumultuous development process. The purpose of this study is to examine how two public universities in Indonesia, i.e. Universitas Negeri Jakarta (UNJ) and Universitas Negeri Surabaya (UNESA), have developed their Chinese language programs. Drawing upon the SWOT analysis theory, this research delves deeper into the strengths, weaknesses, opportunities, and challenges of Chinese language courses in these two public universities in Indonesia. The primary data for this study was collected through survey questionnaires administered to a sample of current and graduated students from Chinese language departments in two public universities in Indonesia. Qualitative data was gathered through interviews conducted with department heads and Chinese language instructors. Secondary data was obtained from books, journal articles, and dissertations related to the study of Chinese education. The research findings reveal the strengths, weaknesses, opportunities, and challenges faced by the Chinese language departments in these two public universities during their development process, and provide strategies for further improvement in these areas. Finally, considering the context of the "Belt and Road Initiative" (BRI), this study offers insights and recommendations for the future development of the Chinese language in Indonesia. The data and conclusions of this research can serve as a resource for future researcher.